LABILE AND NON LABILE FRACTIONS OF SOIL CARBON UNDER DIFFERENT LAND USES AND DEPTHS IN SOUTH KASHMIR - RAZA, MONISA; ALI, TAHIR (The Bioscan, 2018)
Soil samples were collected from surface and sub-surface under four lands uses namely agriculture, forest, horticulture and grassland. In case of agriculture and grassland samples were collected from two depths viz. 0-15 and 15-30 cm while as in case of horticulture and forest samples were collected from three depths namely 0-15, 15-30 and 30-45 cm. Soil samples were analyzed for very labile, labile, less labile and non labile carbon.The highest mean values of TOC viz., 106.47 and 90.88 g kg-1 at 0-15 and 15-30 cm, respectively were recorded under forestland which were followed by grass land having value of 84.67 and 73.49 g kg-1respectively. Very labile and labile carbon were highest in grassland land use with a value of 16.10 and 5.26g kg-1 respectively in 0-15 cm soil depth while as less labile and non labile carbon were highest in case of top layer (0-15 cm) of forest land use with mean values of 7.93 and 78.08g kg-1 respectively. It was observed that these forms were in the order; non labile > very labile > less labile > labile under all land uses. In general, a depth-wise decrease in content of both labile carbon fractions and non labile carbon was observed.